The dynamic relationship between bank risk and corporate governance in Africa - Simms Mensah Kyei; Nereida Polovina; Seyram Pearl Kumah (Cogent Business & Management, 2022)
This paper investigates the nexus between corporate governance and bank risk in Africa using annual data of 635 banks from 48 countries for the period 2000 to 2019 in a panel GMM approach. Our bank risk variables are loan loss provision to net interest revenue (LLPNR) and loan loss reserve to gross loan (LLRGL). The corporate governance variables are board size, female directors, role duality, board meetings, and independent directors. Findings indicate that bank risk measured by LLPNR has significant negative association with female directors, role duality, and frequent board meetings. However, bank risk measured by LLRGL has significant negative connections with board size, and independent directors, but positive connections with female directors and board meetings. This study provides a guide to regulators, shareholders, and management of banks in adopting appropriate corporate governance practices to reduce risk.
Keywords: 650; Africa; Corporate Governance; Bank Performance; Bank Risk